Upaya Peningkatan Keterampilan Kru Kapal Dalam Penggunaan Teknologi Navigasi Kapal - Sandy Wahyu Purnomo; Dapid Rikardo; Joko Sulistianto; Vidiana Anggeranika (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2023)
The purpose of this research is to improve the skills of the crew in the use of navigation technology on board (case study of graduates of the Banten Shipping Polytechnic). This study uses a qualitative method, the population of this study is more than 50 people consisting of management and lecturers of the shipping polytechnic and more than 100 students of the shipping polytechnic. The results of this study through the Analytical Hierarchy Process (AHP) which will calculate hierarchically from each research criteria for each respondent. The results of the analysis of this study are in the form of a priority scale that shows the order of the first factor to the last priority position which causes the quality of the crew to decline along with the parties that have the most influence on the quality produced by the crew. The priority scale of each criterion obtained is the most important criterion that affects the quality of ship crews from graduates of training participants at the Banten Shipping Polytechnic, namely aspects of curriculum/teaching materials that place rank 1 (one) with the highest matrix value 0.5047255107, aspects of the number of hours of study place rank 2 (two) with the matrix value 0.3037629869, the aspect of infrastructure is ranked 3 (three) with the matrix value 0.1275744589, the aspect of facilities is ranked 4 (four) with the matrix value 0.0482186131, and the aspect of the number of teachers is ranked 5 (five) with the matrix value 0.0157184303. The results obtained after the ship's crew implemented the curriculum were that the ship's crew could operate the navigation tools according to what was taught in the Banten Shipping Polytechnic curriculum. The conclusion in this study is that the most important effort in improving the quality of crew skills in the field of navigation technology for graduates of the Banten Shipping Polytechnic is the curriculum and teaching materials used in the education process at the Banten Shipping Polytechnic.